Histopathological Analysis of Gills, Liver, and Kidneys of Nile Tilapia (Oreochromis niloticus) Affected by Hot Lapindo Mud in Porong River, Sidoarjo-East Java - Wahidi, Budi Rianto; Hakimah, Nisa; Suhermanto, Achmad; Triyastuti, Meilya Suzan; Utami, Diah Ayu Satyari (Department of Aquaculture, 2025)
Direct discharge of Lapindo hot mud resulted in abundant toxic substances in the Porong River. The impact extended beyond water quality, affecting fish in the river the Porong River which is their habitat. This study aims to characterize the histopathology of Nile tilapia affected by hot mud and assess the environmental conditions of the Porong River. Histopathological analysis revealed edema, congestion, hyperplasia, fusion, and necrosis in gill lamellae. The kidneys exhibited degeneration, inflammation, edema, hemorrhage, and necrosis, while the liver showed hydropic degeneration, vacuolization, congestion, and necrosis. These results indicate that the toxic substances in the hot mud affect the organ conditions of Nile tilapia in the water.